Calcium Phosphate-Coated Lipid Nanoparticles as a Potential Tool in Bone Diseases Therapy - Simona Sapino (MDPI AG, 2021)
The treatment of bone diseases (including osteoporosis, osteoarthritis, and bone cancer) often results in reduced efficiency and/or adverse reactions due to the fact that it is not specifically targeted to the site of action. The employment of a suitable carrier should increase drug location to the site of bone disease. The purpose of this study is to prepare and characterize lipid nanoparticles (NPs) coated with calcium phosphate (CaP-NPs). A coating method, to date used only to obtain liposomes covered with CaP, is herein partially-modified to prepare CaP-coated lipid NPs. An extensive physico-chemical characterization was achieved by employing several techniques (DLS, SEM and TEM, and both combined with EDS, XRD, and FTIR) that confirmed the feasibility of the developed coating method. Preliminary uptake studies on human osteosarcoma cells (U-2OS) were performed by entrapping, as a lipid probe, Sudan Red III in NPs. The obtained data provided evidence that CaP-NPs showed higher cell accumulation than uncoated NPs. This result may have important implications for the development of drug loaded CaP-NPs to be tested in vitro with a view of planning future treatment of bone diseases, and indicate that CaP-NPs are potential vehicles for selective drug delivery to bone tissue.